Breeding major food staples - Kang, Manjit S.; Priyadarshan, P. M. (Blackwell Pub., 2007)
As the worlds population increases the need to produce greater quantities of major staple crops such as wheat, rice, maize, potato, cassava, soybean, sweet potato, barley, and banana in order to sufficiently feed the people of the world continues t.